Early ethics: Exploring moral intuition and maternal Influence in preschool children - María G. Jean-Tron; Juan Garduño-Espinosa; Diana Ávila-Montiel; Gina C. Chapa-Koloffon; Oscar A. Resendez-Berber; Elizabeth Cruz Cruz; Guillermo Salinas-Escudero; Onofre Muñoz-Hernández (PLoS ONE, 2026)
The purpose of this study was to evaluate the moral intuitions of mothers and children aged 3–6 (n = 75). Methods: Five dilemmas were applied. The agreement between mother and child responses was evaluated, as were trends in agreement between girls and boys. Kappa statistics and Spearman’s correlation analyses were conducted. McNemar’s test was administered to assess the Double Effect Doctrine and the Contact Principle. Outcome: In general, children responded to moral dilemmas similarly to their mothers. However, no significant agreement was found between mothers and children when evaluating each dilemma. Although the children’s answer patterns were similar to those of their mothers, the presence of neither the Double Effect Doctrine nor the Contact Principle could be identified in children. Conclusions: While there are some similarities between preschoolers and their mothers when responding to moral dilemmas, the integration of deontological principles in the resolution of ethical dilemmas in the children studied has not been achieved. Mothers in the study use these principles, which support the previous related evidence.